2001
DOI: 10.1185/030079901317010739
|View full text |Cite
|
Sign up to set email alerts
|

Oral Montelukast Versus Inhaled Beclomethasone in 6- to 11-year-old Children with Asthma: Results of an Open-label Extension Study Evaluating Long-term Safety, Satisfaction, and Adherence with Therapy

Abstract: This 6-month, open-label extension study of a previously described base study compared oral montelukast with inhaled beclomethasone in terms of safety, forced expiratory volume in one second (FEV1) measurements, parent and patient satisfaction with treatment, asthma-related medical resource utilization, school absenteeism, and parental work loss in children with asthma. A total of 124 of 266 asthmatic children, 6 to 11 years of age, who enrolled in the base study entered a 6-month open-label extension study (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 0 publications
1
44
0
1
Order By: Relevance
“…Our finding that adherence to LTRAs and ICS/LABAs is better than adherence to ICSs is supported by previous studies. A study by Maspero and colleagues found that adherence to montelukast, an LTRA that is administered orally, is greater than to inhaled beclomethasone, an ICS, and children and parents reported that montelukast was more convenient and less difficult to use (25). Another study that examined prescription refills found that adherence to montelukast was significantly greater than to an ICS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that adherence to LTRAs and ICS/LABAs is better than adherence to ICSs is supported by previous studies. A study by Maspero and colleagues found that adherence to montelukast, an LTRA that is administered orally, is greater than to inhaled beclomethasone, an ICS, and children and parents reported that montelukast was more convenient and less difficult to use (25). Another study that examined prescription refills found that adherence to montelukast was significantly greater than to an ICS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the four studies scored 5 out of a possible 5 points on the Jadad scale (31)(32)(33), indicating appropriate randomisation and double-blinding techniques and documentation of losses and withdrawals. The fourth study scored 3 out of 5, as blinding methods were not employed (34). Two studies reported adequate methods for allocation concealment (32,33), the third study's methods were not described (31) and concealment of allocation was not used in the fourth study (34).…”
Section: Methodological Qualitymentioning
confidence: 97%
“…Так, в многоцентровом открытом 6-месячном наблюдении [21] по изучению эффективности, безопасности и удовлетворенности терапией монтелукастом в сравнении с ингаляционным глюкокортикостероидом беклометазоном приняли уча-стие 124 ребенка в возрасте 6-11 лет с бронхиальной астмой. Показатели общей эффективности и безопас-ности были сходными и не имели достоверных различий.…”
Section: приверженность лечениюunclassified